Molecular markers in colorectal carcinoma – the Western Australian experience - Kamiński, Artur; Joseph, David (Contemporary Oncology/Współczesna Onkologia, 2003)
Colorectal carcinoma (CRC) is a common malignancy in both males and females. Current treatment modalities include surgery, chemotherapy, and irradiation of rectal lesions. Despite these interventions, however, there is considerable variance in treatment success. This has been observed in same stage tumours treated with standardised surgical and chemo-therapeutic schedules. It has been postulated that these variations arise due to inherent differences in the tumour characteristics, in particular their molecular profiles. Identification of patient groups who are likely to respond to selected therapies may allow more appropriate patient selection for treatment whilst avoiding treatment related side effects. In order to achieve this, a number of studies have been undertaken at Sir Charles Gairdner Hospital in Western Australia. These have focused on previously identified molecular markers that may be of prognostic value in CRC. They include p53, K-ras, microsatellite instabilty, methylation, methylene-tetra-hydro-folate reductase (MTFHR) polymorphism, and transforming growth factor (TGF) beta type II. There are a number of other markers that have been found to be associated with CRC. Although not formally tested in our institution, a brief overview has been appended for completeness. These include dihydropyrimidine dehydrogenase (DPD), thymidylate synthase (TS), thymidine phosphorylase (TP), vascular endothelial growth factor (VEGF), and the bcl-2 gene.